Development of pragmatic skills among 3-4 years old preschooler children in rural region of Gurugram District of Haryana: An Exploratory study - Sarin, Meghavi; Kumar, Vijay; Raj, Riya; Mathew, Grace Mariam (Indonesian Journal of Education and Pedagogy, 2025)
This study investigates on the pragmatic skills development in preschoolers of rural region. A total of 67 participants were the preschoolers of rural region school. Based on the school records, children of nursery grade level in the age groups of 3 to 4 years were considered. Pragmatic parameters using PPT assessment tools check for speech acts, presuppositions, conversational interactions, and non-verbal signals. The results have shown component wise responses on pragmatic profile test: communication functions, response to communication, interaction and conversations, and contextual variations. Children with in naturalistic contexts learn more accurate representations of their pragmatic abilities. Future research should explore these dynamics of pragmatic development, considering the influence of environment and familiarity on children's social communication skills. Teacher in schools also tries to provides more language advancing input and are usually more supportive to language learning for like preschool children.